Kinetic-Catalytic Spectrophotometric Determination of Ruthenium(III) Using the Oxidation of Neutral Red by Metaperiodate in Cationic Micellar Medium - Keyvanfard, Mohsen (Asian Journal of Chemistry, 2010)
A simple, selective catalytic method has been developed for determination of ruthenium(III) based on its catalytic effect on the oxidation of neutral red by metaperiodate in micellar medium. The reaction rate was controlled specrophotometrically by controlling the dye absorbance at 523 nm. The optimized conditions made it possible to determine ruthenium(III) in the range of 0.001-0.14 μg/mL (ΔA = 3.2044CRu + 0.001) and with a detection limit of 0.77 ng/mL. The relative standard deviation of 0.020 and 0.06 mg/mL Ru(III) was 2.3 and 1.4 %, respectively. The proposed method has been successfully applied for analysis of trace amounts of ruthenium(III) in real samples.